The Analysis of Patient Safety Culture in Hospitals - Yusuf Susanto; Nur Hidayah (Devotion: Journal of Research and Community Service, 2022)
Patient safety is a global issue in the world. Patien safety is very important in the Healthcare. This is one indicator of the success of a hospital so that patients feel safe, comfortable and satisfied. This paper aims to analyze factors influencing patient safety culture at the hospital.             The methode of this paper is literature review by searching the library online using the Mendeley Library, Pubmed search instrument, Sage Journal, Google Scholar, Neliti Library. The keywords used are "patient", "safety culture", "hospital", "and "patient safety dimensions" using limits, studies conducted at the hospital to hospital employees, publications English and Indonesian, the last 10 years publication. With the search method, initially there were 1800 articles, 15 of which met the criteria, published until 2021. The results of the analysis from the review indicate that the patient safety culture is influenced by various factors, including perceptions of management, work team support, work stress, job satisfaction towards the patient safety culture in the hospital. Teamwork, leadership, communication in hospitals is a necessary factor in implementing a patient safety culture.